Pengaruh Beban Kerja dan Lingkungan Kerja Terhadap Kinerja Karyawan Melalui Kepuasan Kerja pada PT. X - Uma, Aulia Talitha; Swasti, Ika Korika (Ekonomis: Journal of Economics and Business, 2024)
This study aims to determine the influence of workload and work environment on employee performance through employee job satisfaction at PT. X. This type of research is a quantitative study with primary data and uses a questionnaire technique with a Likert scale of 5 points for a sample of 64 respondents. The data obtained was then analyzed using Partial Least Square (PLS). The results showed that overall employee performance was influenced by workload, work environment, job satisfaction, and the rest by other variables outside the research model. Workload has a non-significant negative effect on employee performance, work environment has a significant positive effect on employee performance, workload has a significant negative effect on job satisfaction, work environment has a significant positive effect on job satisfaction, job satisfaction has a significant positive effect on employee performance, job satisfaction has mediated workload on employee performance with a significant negative relationship, job satisfaction mediates the work environment on employee performance with a significant positive relationship.